دور البنوك التجارية في تمويل المشاريع المصغرة في الجزائر -حالة ولاية المسيلة- - دغفل زينب (University of M'Sila, 2024)
This study dealt with the role of commercial banks in financing small projects in Algeria –the case of the state of M’sila, with the aim of highlighting the contribution of commercial banks in supporting the establishment and financing of small projects. in order to clarify this, the concept of commercial banks, their functions, sources of funds and everything related to them was discussed in the theoretical aspect. We also shed light on mini-projects and their various concepts and sources of financing. We also touched on the issue of financing through its concept and forms, then the relationship of commercial banks to mini-projects and the financing formulas that commercial banks grant to mini-projects. We also touched on the development of mini-projects in Algeria and the role of government bodies specialized in supporting, creating and creating job positions. As for the practical aspect, we shed light on the reality of the contribution of commercial banks to financing small projects in the state through a study of three active commercial banks in the state of M’sila. The study concluded that commercial banks, within the framework of support and financing agencies, contribute to financing small projects in the state.
تناولت هذه الد ا رسة دور البنوك التجارية في تمويل المشاريع المصغرة في الج ا زئر –حالة ولاية المسيلة بهدف إب ا رز مساهمة البنوك التجارية في دعم إنشاء وتمويل المشاريع المصغرة ومن أجل توضيح ذلك تم التطرق في الجانب النظري إلى مفهوم البنوك التجارية ووظائفها ومصادر أموالها وكل ما يتعلق بها، كما سلطنا الضوء أيضا على المشاريع المصغرة ومختلف المفاهيم الخاصة بها ومصادر تمويلها، كما تطرقنا أيضا إلى موضوع التمويل من خلال مفهومه وأشكاله ثم علاقة البنوك التجارية بالمشاريع المصغرة وصيغ التمويل التي تمنحها البنوك التجارية للمشاريع المصغرة، وتطرقنا أيضا إلى تطور المشاريع المصغرة في الج ا زئر ودور الهيئات الحكومية المتخصصة في دعمها وإنشائها واستحداث مناصب الشغل . أما فيما يخص الجانب التطبيقي فقد سلطنا الضوء على واقع مساهمة البنوك التجارية في تمويل المشاريع المصغرة بالولاية من خلال د ا رسة ثلاثة بنوك تجارية ناشطة في ولاية المسيلة، وقد توصلت الد ا رسة إلى أن البنوك التجارية وفي إطار تطبيق برنامج الدولة الخاص بتقديم قروض مدعمة للمشاريع المصغرة في إطار وكالات الدعم والتمويل فإنها تساهم في تمويل المشاريع المصغرة بالولاية.
Keywords: commercial banks; small projects; financing; subsidized loans.; البنوك التجارية، المشاريع المصغرة، التمويل، قروض مدعمة.